Kvantově chemické pojetí návrhu léčiv - Pecina, Adam (2016)
Computational approaches have become an established and valuable component of pharmaceutical research. Computer-aided drug design aims to reduce the time and cost of the drug development and also to bring deeper insight into the inhibitor binding to its target. The complexity of biological systems together with a need of proper description of non-covalent interactions involved in molecular recognition challenges the accuracy of commonly used molecular mechanical methods (MM). There is on the other side a growing interest of utilizing quantum mechanical (QM) methods in several stages of drug design thanks to increased computational resources. This doctoral thesis's topic is the QM-based methodology for the reliable treatement of intermolecular interactions. It consists of eight original publications devided into three topics and an accompanying text that aims to emphasize selected outcomes of the work. Firstly, the nature of nonclassical non-covalent interactions - so called σ-hole bonding - is studied by high-level QM methods. The strength and origin of halogen-, chalcogen- and pnicogen bonded model systems in extended datasets are accurately explored by coupled cluster QM method (CCSD(T)/CBS) and symmetry adapted perturbation theory (SAPT). The second part is devoted to three pharmaceutically...